A Fatty Acid Glycoside from a Marine-Derived Fungus Isolated from Mangrove Plant Scyphiphora hydrophyllacea - Wen-Li Mei; Hao-Fu Dai; Tao Yang; Bo Zheng; Wen-Jian Zuo; Yan-Bo Zeng; Hui Wang (Marine Drugs, 2012)
To study the antimicrobial components from the endophytic fungus A1 of mangrove plant Scyphiphora hydrophyllacea Gaertn. F., a new fatty acid glucoside was isolated by column chromatography from the broth of A1, and its structure was identified as R-3-hydroxyundecanoic acid methylester-3-O-α-l-rhamnopyranoside (1) by spectroscopic methods including 1D and 2D NMR (HMQC, 1H-1H COSY and HMBC) and chemical methods. Antimicrobial assay showed compound 1 possessed modest inhibitory effect on Saphylococcus aureus and methicillin-resistant S. aureus (MRSA) using the filter paper disc agar diffusion method.